Profil SGOT, SGPT, dan Kreatinin Pada Pasien MDR TB di RS KRMT Wongsonegoro Semarang - Surati, Surati; Khairunnisa, Afifah; Setyaji, Yoki; Maulana, Mochamad Rizal (Poltekkes Kemenkes Semarang, 2024)
Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacterium tuberculosis. Tuberculosis apabila is not treated immediately or the treatment is not complete can result in complications leading to death. Multidrugs resistant tuberculosis (MDR-TB) is one of the complications where the germ Mycobacterium tuberculosis can no longer bekilled with several Anti-Tuberculosis Drugs (OAT). The prevalence of MDR-TB cases in Semarang City has increased from 35 cases in 2017 to 79 cases in 2018. MDR-TB therapy takes a longer time, which is about 18-24 months. Prolonged exposure to drugs can affect body functions, especially the kidneys and liver organs which play a role in the process of removing toxins and metabolic waste. This study aims to determine the health profile of the kidney and liver organs of MDR TB sufferers through the SGOT SGPT and Creatinine parameters and describe them based on age and age range. This research is adescriptive quantitative research with a cross-sectional approach. Sampling using total samples of 18 patients. The results showed that 33% (n= 6) of patients had increased levels of SGOT and SGPT, while examination of creatinine levels showed that 33% of patients had kidney problems. Men have upnormal SGOT and SGPT levels of 40% ( n=4) compared to women, which is 25% (n=2), while upnormal creatinine levels in men are 40% (n=4) while in women it is 50% (n = 8). Patients over the age of 46 years have the most levels of SGOT SGPT and upnormal creatinine, which is 61% (n=4). The results showed that age and gender had an effect on increasing SGOT SGPT and Creatinine levels in MDR-TB patients.